Origins of Doha and Qatar: Traditional Qatari Homes - Mariam Al Thani (16020516) (2023)
This item is a Illustrated Presentation produced by UCL Qatar as part of the The Origins of Doha and Qatar Project, and is part of Origins of Doha and Qatar: Traditional Qatari Homes School Pack - English collection. The Illustrated Presentation is for 6 - 11 years age groups. This work was illustrated by Sumam Azzam.